Review: Subjective Time Perception, Dopamine Signaling, and Parkinsonian Slowness - Miyawaki, Edison K. (Frontiers in Neurology, 2022)
The association between idiopathic Parkinson’s disease, a paradigmatic dopamine-deficiency syndrome, and problems in the estimation of time has been studied experimentally for decades. I review that literature, which raises a question about whether and if dopamine deficiency relates not only to the motor slowness that is an objective and cardinal parkinsonian sign, but also to a compromised neural substrate for time perception. Why does a clinically (motorically) significant deficiency in dopamine play a role in the subjective perception of time’s passage? After a discussion of a classical conception of basal ganglionic control of movement under the influence of dopamine, I describe recent work in healthy mice using optogenetics; the methodology visualizes dopaminergic neuronal firing in very short time intervals, then allows for correlation with motor behaviors in trained tasks. Moment-to-moment neuronal activity is both highly dynamic and variable, as assessed by photometry of genetically defined dopaminergic neurons. I use those animal data as context to review a large experimental experience in humans, spanning decades, that has examined subjective time perception mainly in Parkinson’s disease, but also in other movement disorders. Although the human data are mixed in their findings, I argue that loss of dynamic variability in dopaminergic neuronal activity over very short intervals may be a fundamental sensory aspect in the pathophysiology of parkinsonism. An important implication is that therapeutic response in Parkinson’s disease needs to be understood in terms of short-term alterations in dynamic neuronal firing, as has already been examined in novel ways—for example, in the study of real-time changes in neuronal network oscillations across very short time intervals. A finer analysis of a treatment’s network effects might aid in any effort to augment clinical response to either medications or functional neurosurgical interventions in Parkinson’s disease.